Maxim’s responsibilities toward food and bike delivery drivers under Law No. 6 Of 2023 (A study in Banda Aceh) - Teuku Hasbulhadi; Arifin Abdullah; Mustem Mustem (Privietlab, 2026)
The emergence of platform-based business models has significantly transformed conventional patterns of employment, raising ongoing debate regarding the legal status of individuals engaged through digital platforms within Indonesia's employment law framework. This study examines the legal responsibility of Maxim, a Russia-based digital transportation and food delivery platform operating in Banda Aceh, in light of Law Number 6 of 2023 on Job Creation. The research employs a normative-empirical juridical approach supported by in-depth interviews with five active Maxim drivers. The analysis is grounded in employment relationship theory, the concept of algorithmic subordination, and principles of labor protection viewed through the lens of social justice. The findings indicate that the three essential components of an employment relationship—namely work, wages, and subordination—are substantively reflected in the legal relationship between Maxim and its drivers, despite the company's formal designation of drivers as